ReLink strategy in diagnosed-but-untreated hepatitis C-positive patients in Germany: report from a single center - Lange, Sarah; Baehr, Christina; Cakman-Hinrichs, Nur Irem; Cron, Katharina; Fengels, Hannah; Gregor, Christina; Matschenz, Katrin; Petersen, Jörg; Steinfurth, Robin; Stoehr, Albrecht; Unger, Stefan; Gil Mir, Maria; Hernández, Candido; Schwenken, Marianna; Buggisch, Peter (Zeitschrift für Gastroenterologie, 2024)
Objective The ReLink project aims to reintegrate diagnosed-but-untreated hepatitis-C-positive patients into medical care and initiate a therapy.Material/methods A retrospective search within the practice management system of a single center in Germany identified among 1965 hepatitis-C-positive patients 100 untreated patients with available contact details and meeting all inclusion criteria. Patients were contacted by 2 contact rounds.Results Out of 100 patients, 64% were male. Most patients (81%) were aged between 30 and 59 years. The patients belonged to high-risk groups for hepatitis C virus infections or had other comorbidities. The majority of patients injected drugs (21%) and/or were currently or had been on substitution therapy (44%); alcohol addiction was also frequent (21%). Out of 25 patients who agreed to an appointment, 10 patients (40%) started therapy and 5 additional patients (20%) agreed to therapy but were not yet able to start or had not yet made a decision. One‑third of patients who agreed to an appointment did not show up.Conclusions Diagnosed-but-untreated patients are an important subgroup of hepatitis-C-positive patients; their recall to the clinic for direct-acting antiviral therapy is possible. However, inaccurate contact information, unresponsiveness to outreach, and further reluctance to attend doctor appointments limited the overall impact of this program. Regular review of the patients’ contact details may facilitate both follow-up and recall.
Keywords: Hepatitis C elimination; ReLink strategy; diagnosed-but-untreated patients; linkage to medical care; patients lost to follow-up; difficult-to-treat person